Analysis of Inquiries for Psychosocial Counselling Services and Support in the Context of COVID-19 - Лях, Татьяна; Лехолетова, Марина; Скіпальська, Галина (Київський національний університет імені Тараса Шевченка, 2021)
Authors of the article analyze inquiries of populations in crisis for social and psychological counselling and support, in particular, associated with domestic and gender-based violence, in the regions of Ukraine which suffer the most due to the COVID-19 pandemic. The sample includes individuals who receive social services provided by state agencies and civil society organizations in different cities of Ukraine, namely, in differentterritorial communities. The number of respondents selected among clients of social services providers was 357 people. The survey method has provided authors with better understanding of services delivered to these populations, and which of them were in demand; impact of COVID-19 pandemic on families of social services recipients; needs of residents of communities and major providers of social and psychological services in these communities. Findings of the study: increased number of conflicts in families; increased number of people who seek social and psychological counselling and support due to domestic violence; predominance of individual counselling services over other social services; low rates of family counselling and group work with all family members; the need to increase the number of specialists who provide services and social and psychological support tosurvivors of domestic violence; the need to improve preventive measures and public awareness activities to combat negative phenomena and, simultaneously, prevent domestic violence, both in small communities and at the regional level. It was found that it is appropriate to increase the number of providers of social and psychological counselling and support to survivors of domestic violence. It was also found that social support is considered to be an effective type of social service when working with survivors. The study was conducted during 2020 within the project "Gender-sensitive emergency assistance to overcome the consequences of the COVID-19 crisis and strengthen gender equality in Ukraine" implemented by the ICF "Ukrainian Foundation for Public Health" with support of UNFPA.

Проаналізовано запити щодо соціально-психологічної допомоги та підтримки кризових категорій населення в найуразливіших до COVID-19 регіонах України, зокрема з питань протидії домашньому насильству та насильству за ознакою статі. За результатами дослідження виявлено зростання кількості конфліктів у сім'ях; збільшення кількості осіб, які звертаються за соціально-психологічною підтримкою та допомогою через жорстоке поводження в сім'ї; переважання індивідуальних консультаційних послуг над іншими видами соціальних послуг. Дослідження проводилося в межах проєкту "Гендерно-чутлива екстрена допомога з подолання наслідків кризи СОVID-19 та посилення гендерної рівності в Україні", реалізованого МБФ "Українська фундація громадського здоров'я" протягом 2020 р. за підтримки Фонду ООН у галузі народонаселення в Україні.
Аналіз запитів населення щодо отримання соціально-психологічної допомоги та підтримки в умовах COVID-19
Keywords: COVID-19; domestic violence; support; difficult life situation; social services; social and psychological counselling; territorial communities; COVID-19; домашнє насильство; підтримка; складні життєві обставини; соціальні послуги; соціально- психологічна допомога; територіальні громади